Dermatofibrosarcoma protuberans of the foot in a 72-year-old man: A case report - Vighe, Saurabh; Chauhan, Amritasingh; Deshmukh, Rajesh; Mankar, Chandrashekhar (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Not applicable